FRI0216 STEROID SPARING EFFECT, LOWER INCIDENCE OF DISEASE RELAPSE AND DIABETES IN GIANT CELL ARTERITIS TREATED WITH IMMUNOSUPPRESSORS AB INITIO OR VERY EARLY: A MULTICENTER RETROSPECTIVE CASE-CONTROL STUDY. (2nd June 2020) - Quartuccio, L.; Isola, M.; Bruno, D.; Treppo, E.; Gigante, L.; Angelotti, F.; Capecchi, R.; Vitiello, G.; Cavallaro, E.; Tavoni, A.; Bosello, S. L.; Cammelli, D.; et al.
Abstract : Background: Glucocorticoids (GC) are associated with serious side effects in giant cell arteritis (GCA). Immunosuppressive therapies (IT) gave conflicting results in GCA, regarding GC sparing effect. Recently, tocilizumab by blocking IL-6, has been licensed as first biologic treatment for GCA, being clinically effective and saving GC (1). Objectives: To evaluate the usefulness of IT for GCA in: 1) minimizing the rate of GC-induced adverse events (AEs) and 2) reducing the risk of relapse. Methods: A multicenter retrospective case-control study included 165 GCA was performed. The first group of patients (GCA-IT) included 114 patients who were treated with at least one IT given ab initio or within 3 months from the start of GC. The control group included 51 GCA who received only GC or an IT later than 3 months (GCA-steroid). The primary endpoints were the rate of GC-related side effects: infections, hospitalized infections, new onset systemic arterial hypertension, GC-induced diabetes and osteoporotic fractures. Results: Methotrexate up to 20 mg/week (138 patients), followed by cyclophosphamide (48 patients) and tocilizumab (27 patients) were the most frequently used IT. No difference was observed as concerns the follow-up time between the two groups [48.5 (IQR 26-72) vs 40 (IQR 24-69), p=0, 3, rank-sum test)]. The two groups were similar as concerns sex (p=0, 13), while the first group (69±8 yrs) was slightly younger than the second one (72±7 yrs) (p=0, 005). Comorbidity was similar between groups. Patients in the GCA-IT group showed a significant lower incidence of GC-induced diabetes (8/114, 7% vs 12/51, 23, 5%; p=0, 003, chi-square test), while no differences were documented for rate of infections (p=0, 64), including hospitalized infections (p=0, 44), new onset systemic arterial hypertension (p=0, 68), or osteoporotic fractures (p=0, 32). Forty-four patients in the GCA-IT group (38, 6%), while 34 patients in the GCA-steroid group (66, 7%) experienced at least one relapse (p=0, 001, chi square test). There was no difference in terms of time to first relapse between the two groups (p=0, 53, log-rank test). GCA-IT group was exposed to lower dose of GC at first (p<0, 0001, rank-sum test) and third (p<0, 0001, rank-sum test) month, while no differences were recorded at the other time points. Clinical outcomes were similar between the two groups. Conclusion: Very early introduction of IT in GCA provided a greater steroid sparing in the first 3 months of treatment, leading to a lower incidence of diabetes. Relapse rate was even lower. IT was usually well tolerated without an increase incidence of infections. A randomized prospective trial is required to support this strategy in the management of GCA. References: [1]Hellmich B, et al. 2018 Update of the EULAR recommendations for the management of large vessel vasculitis. Ann Rheum Dis. 2020;79:19-30. Disclosure of Interests: Luca Quartuccio Consultant of: Abbvie, Bristol, Speakers bureau: Abbvie, Pfizer, Miriam Isola: None declared, Dario Bruno: None declared, Elena Treppo: None declared, Laura Gigante: None declared, Francesca Angelotti: None declared, Riccardo Capecchi: None declared, Gianfranco Vitiello: None declared, Elena Cavallaro: None declared, Antonio Tavoni: None declared, Silvia Laura Bosello: None declared, Daniele Cammelli: None declared, Salvatore De Vita Consultant of: Roche, GSK, Speakers bureau: Roche, GSK, Novartis, Elisa Gremese Speakers bureau: Abbvie, BMS, Celgene, Jannsen, Lilly, MSD, Novartis, Pfizer, Sandoz, UCB